Differential Pulse Voltammetric Determination of Sulfite in Fruit Juice Samples Using an Unmodified Screen-Printed Graphene Electrode - Phuangkum, Kanokphon; Phasuk, Suphicha; Sanchayanukun , Phetlada; Muncharoen, Sasithorn (Burapha Science Journal, 2026)
Background and Objectives : In recent years, consumers have become increasingly health-conscious and tend to consume fruit juices more frequently due to their valuable content of essential vitamins and minerals. However, commercially packaged fruit juices often contain food additives such as sulfites, which serve as preservatives to extend shelf life and maintain product quality. However, excessive intake of sulfites can pose potential health risks. Therefore, the development of analytical methods that are rapid, accurate and cost-effective for sulfite determination is essential. Electrochemical techniques, particularly Differential Pulse Voltammetry (DPV) combined with Screen-Printed Electrodes (SPEs) have gained considerable attention due to their high analytical sensitivity, low cost, minimal sample preparation requirements and suitable on-site analysis. In this study, an unmodified Screen-Printed Graphene Electrode (SPGE) was employed owing to its outstanding electrical conductivity, chemical stability and mechanical strength including robust structural properties. The objective of this research was to develop and apply the unmodified SPGE coupled with DPV for the determination of sulfite in commercially available fruit juice samples, as well as to evaluate the analytical performance in terms of sensitivity, accuracy and precision including feasibility of this method for practical field applications in the future. Methodology : The sulfite analysis was carried out using DPV under optimized conditions. Standard sulfite solutions with concentrations ranging from 25 to 500 µM were prepared, and 80 µL of each solution was used for measurement. The applied potential was set between 0.00 and 1.50 V with a step potential of 20 mV, modulation amplitude of 80 mV, modulation time of 50 ms and interval time of 200 ms. The electrochemical behavior of the electrode was examined by Cyclic voltammetry (CV), while the optimal analytical conditions were determined by studying the effects of buffer pH and various DPV parameters, including step potential, modulation amplitude, modulation time and interval time considering the current response and peak characteristics. Analytical performance was evaluated in terms of linearity, limit of detection (LOD) and limit of quantitation (LOQ). Additionally, the precision of the method was assessed through repeatability and reproducibility tests in terms of relative standard deviation (%RSD). The study of interferences was investigated using compounds commonly present in fruit juices for instant ascorbic acid, citric acid, potassium sorbate and sucrose. For real sample analysis, nine (9) types of fruit juice such as coconut, apple, mixed fruit and vegetable, orange, lychee, longan, guava, strawberry and pandan were purchased from a local supermarket. All samples were analyzed using the unmodified screen-printed graphene electrode under the optimized DPV conditions. Main Results : The screen-printed graphene electrode (SPGE) exhibited a significantly higher current response compared to the screen-printed carbon electrode (SPCE) indicating superior electrical conductivity as previously reported for graphene-based materials. This observation was consistent with the electrochemical impedance spectroscopy (EIS) results, which showed that the SPGE possessed a lower charge transfer resistance. The effect of pH on the voltametric response behavior of sulfite was also examined. The results revealed that the current increased within the pH range of 2.0 – 3.5 and decreased at pH values above 5.5. Therefore, pH 3.5 was selected as the optimal condition for subsequent measurements. For differential pulse voltametric parameters, the sharpest and most stable peak was obtained under the following conditions of step potential of 20 mV, a modulation amplitude of 80 mV, a modulation time of 50 ms and an interval time of 200 ms. These parameters provided a well-defined peak with minimal background noise, ensuring reliable quantitative analysis. Under the optimized conditions, the developed method demonstrated a linear response for sulfite determination within the concentration range of 25 – 500 µM with a correlation coefficient (r²) of 0.9945, indicating excellent linearity. The limits of detection (LOD) and quantification (LOQ) were found to be 12.27 µM and 40.92 µM, respectively. Interference studies revealed that sucrose caused the least interference, whereas ascorbic acid produced the most noticeable interference due to its electroactive nature. Nevertheless, the magnitude of this interference remained within an acceptable range and did not compromise the overall analytical performance. Application of the method to nine commercially available fruit juice samples yielded recovery values ranging from 80 – 120%, which fall within the acceptable limits for standard analytical procedures (AOAC standard). These results confirm that the proposed method provides satisfactory accuracy and precision. Overall, the findings indicate that the developed method is suitable for sulfite determination in fruit juice beverages and gives potential for practical implementation in quality control laboratories. Conclusions : This study successfully developed a method for the rapid and efficient determination of sulfite in fruit juice using DPV coupled with an unmodified screen-printed graphene electrode (SPGE), achieving optimal results at an electrolyte pH of 3.5. The method demonstrated high analytical performance, exhibiting a wide linear range of 25 – 500 µM (r2 = 0.9945), low limits of detection and quantification of 12.27 µM and 40.92 µM, respectively and excellent precision with repeatability and reproducibility values of 6.04% and 5.68%, respectively. Furthermore, the method proved highly reliable when tested with real fruit juice samples, %recovery in the range of 80 – 120%, thereby confirming its accuracy, precision and stability for practical quality control applications.